Mosquito-borne diseases in India over the past 50 years and their Global Public Health Implications: A Systematic Review - Naik, B. Reddya; Tyagi, B. K.; Xue, Rui-De (Journal of the American Mosquito Control Association, 2023)
Mosquito-borne diseases (MBDs) pose a significant public health concern globally, and India, with its unique eco-sociodemographic characteristics, is particularly vulnerable to these diseases. This comprehensive review aims to provide an in-depth overview of MBDs in India, emphasizing their impact and potential implications for global health. The article explores distribution, epidemiology, control or elimination, and economic burden of the prevalent diseases such as malaria, dengue, chikungunya, Japanese encephalitis, and lymphatic filariasis, which collectively contribute to millions of cases annually. It sheds light on their profound effects on morbidity, mortality, and socioeconomic burdens and the potential for international transmission through travel and trade. The challenges and perspectives associated with controlling mosquito populations are highlighted, underscoring the importance of effective public health communication for prevention and early detection. The potential for these diseases to spread beyond national borders is recognized, necessitating a holistic approach to address the challenge. A comprehensive literature search was conducted, covering the past five decades (1972–2022), utilizing databases such as Web of Science, PubMed, and Google Scholar, in addition to in-person library consultations. The literature review analyzed 4,082 articles initially identified through various databases. After screening and eligibility assessment, 252 articles were included for analysis. The review focused on malaria, dengue, chikungunya, Japanese encephalitis, and lymphatic filariasis. The included studies focused on MBDs occurrence in India, while those conducted outside India, lacking statistical analysis, or published before 1970 were excluded. This review provides valuable insights into the status of MBDs in India and underscores the need for concerted efforts to combat these diseases on both national and global scales through consilience.